Design Of Low Noise Amplifier For Ultra-Wideband (UWB) Applications Using Silterra 0.18 μm Cmos Technology - Ooi, Wei Ching (Universiti Sains Malaysia, 2006)
The low noise amplifier (LNA) for Ultra Wideband (UWB) mode 1 application, which is covering a frequency range from 3.1 GHz to 4.9 GHz. LNA is the first gain element in the receiver architecture. It is designed for Direct Conversion (DICON). Based on these system characteristics, inductive degenerated common source LNA was designed using Silterra 0.18 μm process. UWB system with multi band Orthogonal Frequency Division Multiplexing (MBOA) was chosen over Direct Sequence Spread Spectrum (DSSS) due to its full optimization of the allocated 7.5 GHz bandwidth. This LNA consumes 5.9 mA of total current from a 1.8 V dc power supply. LNA is designed using inductive degenerated common source amplifier, which is widely used in narrow band design. For UWB application such as wideband matching was implemented to extend the bandwidths of a narrow band system. In this project, wideband reactive matching following by LC Chebyshev band pass filter is utilized. The LC band pass filter utilizes the transformation from low pass network to band pass network is presented. Impedance and frequency scaling are used in filter transformation from a low pass filter to a band pass filter. The wideband filter, as input matching network, is designed on chip for better integration. Three test cases were carried out using LNA with ideal inductors, ASITIC inductors and SIL18RF inductors. For the ideal LNA, higher power consumption of 11.25 mW is observed at 1.9 GHz bandwidth, 14.1 dB power gain with gain flatness of ±0.25 dB, input and output match of -10 dB over its frequency range, noise figure of 2.9 dB and third order intercept point of -6.2 dBm with ideal inductors is . However, using ASITIC inductor, the gain of LNA is dropped to 13.2 dB with gain flatness of ± 1.5 dB exhibiting higher noise figure of less than 6 dB with the same input and output matching and comparable third order intercept point. On the other hand, using SIL18RF inductor, the gain of LNA is further decreased to 8.5 dB, exhibiting noise figure of less than 4.3 dB with poorer input and output matching of -9.5 dB and -6.1 dB, respectively. Measurements were carried out on MAX 2654 evaluation kit at a frequency scaling of 1.6 GHz, exhibiting a 9 dB gain, input and output match of -7 dB and -14 dB, respectively and higher power consumption, 15 mW.